ANALISIS KONTRIBUSI ALOKASI DANA PENDIDIKAN TERHADAP PROGRAM PENINGKATAN MUTU PENDIDIKAN ANAK USIA DINI (PAUD) PADA DINAS PENDIDIKAN KABUPATEN KEBUMEN - Indra Purnomo, Kardianto (Jurnal E-Bis (Ekonomi-Bisnis), 2019)
This research intends to know how much contribution of funding allocation to the program improving quality of early childhood education. This is based on the program of improving quality of early childhood education is closely related to the allocation of funds provided. Starting from the problems,the purpose of this research are to know how much contribution and effectiveness of funding allocation to the program improving quality of early childhood education. The method used in this research is descriptive research method with quantitative approach. While the data collection method used are observation, questionnaire and documentation. The result of this reseach concluded that contribution of funding allocation to the program improving quality of early childhood education included in the medium (enough) category with the percentage of 46,69% each year. While the effectiveness of the quality improvement program of early childhood with the percentage of 82,6% included in the very effective category.